Estimation of stress in specimens loaded with ultrasonic fatigue machines. (December 2021) - Jacquemain, V.; Ranc, N.; Cheuleu, C.; Michel, V.; Favier, V.; Castelnau, O.; Vinci, D.; Thiaudiere, D.; Mocuta, C.
Highlights: The largest deviation on frequency is caused by the uncertainty on Young's modulus. Frequency deviations from machining are lower than that induced from Young's modulus. The uncertainty in stress estimation using a laser coupled with FEM is 3.2%. The uncertainty in stress estimation using strain gauges is 3%. The uncertainty in stress estimation using XRD is 10%. These uncertainties underline a good agreement in stress amplitude estimation. The stress amplitude was found to vary linearly with the displacement amplitude. The material response at the macroscopic scale can be considered as purely elastic. XRD provides an experimental 1D profile of stress amplitude along the sample length. Abstract: Piezo-electric ultrasonic fatigue machines are used to carry out fatigue tests more rapidly than what is possible using other technologies, at a frequency of 20 kHz . The very high cycle fatigue (VHCF) domain can be studied with these machines as 10 9 cycles are reached within 14 h when specimens are loaded at stress amplitudes below the yield stress or conventional fatigue strength. The estimation of stress in specimens fatigued at high frequency is a current challenge when adopting this technology. This paper discusses the accuracy and reliability of three methods used to estimate stress amplitudes in specimens subjected to VHCF tests at a high loading frequency. Two historically used methods using strain gauges and a laser vibrometer are discussed and compared with a third, recently developed method based on time-resolved in situ X-ray diffraction (XRD). The three methods are applied to estimate the stress amplitude in a pearlitic steel specimen. The experimental artifacts and uncertainties are evaluated quantitatively to compare the benefits and limits of the methods. The experimental results show that the three methods correctly estimate the stress amplitudes applied to fatigued specimens.